2016
DOI: 10.1039/c6ra18991a
|View full text |Cite
|
Sign up to set email alerts
|

Use of dicyanamide ionic liquids for extraction of metal ions

Abstract: A correlation between the extraction capacity of tetraalkylammonium dicyanamide ILs and the nature of the anion of the metal salt was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Dicyanamide ILs are generally obtained by the reaction of the chloride or bromide salt with AgN(CN) 2 . To avoid any silver contamination, TAAILs 29 – 40 were synthesized following a modified protocol of Boudesocque and co‐workers . The corresponding bromide salt is suspended in sodium dicyanamide solution in water (1.5 equivalents) and stirred at room temperature for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicyanamide ILs are generally obtained by the reaction of the chloride or bromide salt with AgN(CN) 2 . To avoid any silver contamination, TAAILs 29 – 40 were synthesized following a modified protocol of Boudesocque and co‐workers . The corresponding bromide salt is suspended in sodium dicyanamide solution in water (1.5 equivalents) and stirred at room temperature for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…[48] Recently,i tw as reported that the dicyanamide (DCA) anion led to remarkable improvements of the viscosity and electrochemicalw indow (EW) of ammonium-,p hosphonium-a nd imidazolium-based ionic liquids leading to be promising candidates for the applications mentioned above. [54][55][56][57] Therefore, we were interested in the combination of the dicyanamide anion with different TAAIL cations and its influence on the physicochemical properties of the resulting materials. To further investigate the structure-property correlation, we synthesized as et of TAAILs with different aryl substituents in the ortho-a nd para-position and differenta lkyl chain lengths (butyl, octyl and dodecyl) with both the DCA anion and the bis(trifluoro-methylsulfonyl)imide (N(SO 2 CF 3 ) 2 ,N Tf 2 )a nion for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The high extraction properties of Dca − based ionic liquids are ascribed to the ability of dicyanamide anion to interact with metallic cations through the formation of metal complexes via their nitrogen atoms [33,34]. The examination of the structure of metal complexes in which the dicyanamide anion acts as a ligand, shows that this anion behaves as a monodentate or bridging ligand [33,34]. It is reasonable to think that the higher extraction yields observed for Cu(II) and Cd(II) compared to those of Ni(II), Co.(II) and Pb(II) are related to their higher affinity for Dca − anion, which favors their transfer from aqueous to ionic liquid phases.…”
Section: Influence Of the Anion Of The Ionic Liquidmentioning
confidence: 99%
“…Although it has high extraction yields, BuNC 2 OC 2 -Dca does not allow considering applications in the field of the purification of industrial effluents because of its solubility in water (≈6%), that is why we focused on the development of more hydrophobic ionic liquids, to reduce the releasing of organic cations in aqueous phase. The high extraction properties of Dca − based ionic liquids are ascribed to the ability of dicyanamide anion to interact with metallic cations through the formation of metal complexes via their nitrogen atoms [33,34]. The examination of the structure of metal complexes in which the dicyanamide anion acts as a ligand, shows that this anion behaves as a monodentate or bridging ligand [33,34].…”
Section: Influence Of the Anion Of The Ionic Liquidmentioning
confidence: 99%
See 1 more Smart Citation